2021
DOI: 10.1101/2021.07.01.21259836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered DNA methylation pattern characterizes the peripheral immune cells of patients with autoimmune hepatitis

Abstract: Objective: AIH is a chronic liver disease of unknown aetiology with favourable response to immunosuppression. Little is known about the impact of methylation modifications on disease pathogenesis. Design: 10 patients with AIH at diagnosis (time-point 1; tp1), 9 with primary biliary cholangitis (PBC) and 10 healthy controls (HC) were investigated. 8/10 AIH patients were also investigated following biochemical remission (time-point 2; tp2). Peripheral CD19(+)- and CD4(+)-cells were isolated to study global DNA m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…83 In addition, epigenetic factors that alter gene expression without changing the nucleotide sequence may also contribute to the clinical expression and phenotype of the disease. 84 Multiple hypo-methylated genes have been described in the CD4 positive and CD19 positive T lymphocytes of patients with autoimmune hepatitis, 85 and the circulating micro-ribonucleic acids miR-21 and miR-122 correlate with laboratory and histological features of liver inflammation. 86 Moreover, outside the major histocompatibility complex, single nucleotide polymorphisms concerning pro-inflammatory as well as regulatory pathways have also been described in autoimmune hepatitis, affecting genes such as those for tumor necrosis factor, CTLA-4/CD28, FAS, TGFγ1, and interleukin-4.…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…83 In addition, epigenetic factors that alter gene expression without changing the nucleotide sequence may also contribute to the clinical expression and phenotype of the disease. 84 Multiple hypo-methylated genes have been described in the CD4 positive and CD19 positive T lymphocytes of patients with autoimmune hepatitis, 85 and the circulating micro-ribonucleic acids miR-21 and miR-122 correlate with laboratory and histological features of liver inflammation. 86 Moreover, outside the major histocompatibility complex, single nucleotide polymorphisms concerning pro-inflammatory as well as regulatory pathways have also been described in autoimmune hepatitis, affecting genes such as those for tumor necrosis factor, CTLA-4/CD28, FAS, TGFγ1, and interleukin-4.…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…A previous clinical study reported a correlation between the DNA methylation status in certain immune cells such as CD4 + and CD19 + lymphocytes and disease activity. Altered expression of enzymes involved in DNA methylation, TET1 and DNMT3A, characterizes lymphocytes in AIH ( 38 ). Further studies are required in order to confirm this association.…”
Section: Epigenetics In Various Liver Diseasesmentioning
confidence: 99%
“…Even though the etiology of AIH is still not clear, there is evidence that the development of the disease is based on genetic predisposition, environmental and epigenetic factors [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, DNA methylation, histone adjustments, and micro-RNAs (miRNAs) are examples of epigenetic alterations that may regulate gene expression even though they do not change the DNA sequence [10]. We recently found DNA methylation changes in circulating immune cells and at the histological level of AIH patients, which were associated with disease activity and influenced by immunosuppressive treatment [12]. This review aims to summarize the recent challenges and advances in AIH diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%